Hymenopellis areolata (Physalacriaceae: Agaricales), a new species from Margalla Hills National Park, Islamabad, Pakistan - Fauzia Razzaq; Abdul Nasir Khalid; Zia Ulllah (European Journal of Taxonomy, 2024)
During exploratory surveys of the fungal diversity in Margalla Hills National Park, Islamabad, we collected a new species of the genus Hymenopellis R.H.Petersen. This is the second report of any species of this genus from Pakistan. Hymenopellis areolata F.Razzaq & Khalid sp. nov. is characterized by an areolate pileus, small basidiospores, and transitional pileipellis (hymeniderm and epithelium) with small pileocystidia. Molecular phylogenetic analyses of the nucleotide sequences of nrITS and nrLSU regions, and morphological data support the description of this new species. A comparison with other closely related species confirmed that the newly described species is distinct from others.